2016
DOI: 10.1136/emermed-2015-205258
|View full text |Cite
|
Sign up to set email alerts
|

Image-based teleconsultation using smartphones or tablets: qualitative assessment of medical experts

Abstract: BackgroundMobile health has promising potential in improving healthcare delivery by facilitating access to expert advice. Enabling experts to review images on their smartphone or tablet may save valuable time. This study aims at assessing whether images viewed by medical specialists on handheld devices such as smartphones and tablets are perceived to be of comparable quality as when viewed on a computer screen.MethodsThis was a prospective study comparing the perceived quality of 18 images on three different d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
20
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
5
2
1

Relationship

2
6

Authors

Journals

citations
Cited by 29 publications
(23 citation statements)
references
References 17 publications
(15 reference statements)
3
20
0
Order By: Relevance
“…Initial assessments within the current project showed that the quality of images taken at point of care with smartphone cameras is good enough to be used for diagnostic support. The results showed that both size and depth of burns could be assessed at least as well using photographs as at bedside and that the image quality of handheld devices can be used as well as computers [18,19]. There are several challenges that need to be considered when evaluating the potential health impact of the system.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Initial assessments within the current project showed that the quality of images taken at point of care with smartphone cameras is good enough to be used for diagnostic support. The results showed that both size and depth of burns could be assessed at least as well using photographs as at bedside and that the image quality of handheld devices can be used as well as computers [18,19]. There are several challenges that need to be considered when evaluating the potential health impact of the system.…”
Section: Discussionmentioning
confidence: 99%
“…This study focused on whether images viewed on handheld devices were perceived by experts as comparable in quality to when viewed on a computer screen [19]. For that purpose, we used different types of images – of burns, skin lesions, radiology, scans, and a non-clinical one – and conducted a survey among clinicians with different backgrounds.…”
Section: Follow-up Design and Outcome Measuresmentioning
confidence: 99%
“…It is valuable for pictures taken for ophthalmology (Maamari 2014). Earlier studies addressed the use of tablets and smartphones in the field of radiology and emergency medicine found that tablets and smartphones were rated equal or better than computer screens (Boissin 2017;Toomey, Rainford & Leong 2014). In the current study, smartphones and tablets have similar subjective image quality (p > 0.05, not significant) as computers.…”
Section: Discussionmentioning
confidence: 99%
“…Mobile devices, such as phones and tablet computers, have started to play an increasingly important role in clinic and research. In clinic, new ways are steadily introduced to record medical images, process them, and to enable quantification for diagnostic purposes (Yamada, Watarai, Andou, & Sakai, 2003;Razdan, Johannes, Kuo, & Bagley, 2006;Mudanyali et al, 2012;Rothman, Gupta, & McEvoy, 2017;Boissin, Blom, Wallis, & Laflamme, 2017). In research, advances in mobile imaging assist in microscopic imaging and spectroscopy (Smith et al, 2011;Skandarajah, Reber, Switz, & Fletcher, 2014;Kazemzadeh et al, 2015;Rojas, Fuentes, & Galvez, 2016;Scherr, Gupta, Wright, & Haselton, 2016).…”
Section: Introductionmentioning
confidence: 99%